2014
DOI: 10.17221/490/2013-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural distillates from Polish varieties of rye

Abstract: We evaluated the effect of Polish cultivars of rye on the dynamics of fermentation and the amount and composition of the by-products in agricultural distillates obtained. The scope of research included the analysis of mashes prepared from the following rye cultivars: Dańkowskie Złote, Dańkowskie Diament, Amilo, and Amber. It has been shown that the use of the cv. Dańkowskie Diament rye had a significant effect on the concentration of acetaldehyde in the distillate obtained. Its content in this distillate was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
2
9
1
Order By: Relevance
“…The starch content of the rye grain used in the study (cv. Dańkowskie Diament) was consistent with the literature data [15]. In turn, the starch content of cereal malts was lower as a result of the development of enzymes hydrolyzing starch to soluble saccharides [16,17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The starch content of the rye grain used in the study (cv. Dańkowskie Diament) was consistent with the literature data [15]. In turn, the starch content of cereal malts was lower as a result of the development of enzymes hydrolyzing starch to soluble saccharides [16,17].…”
Section: Discussionsupporting
confidence: 88%
“…A significant criterion in selecting raw materials for efficient ethanol production is sugar content. Cereal grains are valued for their high efficiency because they are rich in starch [15]. The starch content of the rye grain used in the study (cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent to this, Klosowski and Czuprynski [55] suggested that no statistical differences could be determined between the two strains of the yeast examined and that the differences in fermentation by-products in the final spirit were narrowed down to the raw material used. Pietruszka and St Szopa [58] took this further and demonstrated that differences in the concentration of spirit volatile congeners could be detected between different varieties of rye used as a raw material. The preconditioning of distillers' yeast (M strain) has been proven to have a negative impact on the production of volatile esters [59].…”
Section: Role Of Yeastmentioning
confidence: 99%
“…As a distillers' raw material, cereal grain is valued for its high efficiency because it is rich in starch [38]. The starch content in the used in our study rye grains Dańkowskie Złote cv.…”
Section: The Chemical Composition Of Raw Materialsmentioning
confidence: 99%